Sexual & Reproductive Health Commodities: Measuring Prices, Availability & Affordability Findings and recommendations – Uganda - HEPS (HEPS, 2017)
Good sexual and reproductive health (SRH) is a state of complete physical, mental and social well-being in all matters relating to reproduction for both men and women, including adolescents. Maintaining good SRHVmeans people need access to accurate information and to safe, effective, affordable and acceptable contraception methods of their choice. They must be informed and empowered to protect themselves from sexually transmitted infections and, when necessary, receive timely and affordable treatment. And when they decide to have children, women must have access to services that ensure they have a fit pregnancy, safe delivery and healthy baby. Every individual has the right to make their own choices about their SRH and family planning. Poor reproductive health constitutes a significant portion of the disease burden in developing countries, yet essential reproductive health commodities often are not available to the majority of the population in low and middle-income countries. In Uganda, the lack of access to and use of reproductive health commodities threatens the well-being of individuals, families, and communities due to a number of challenges. The Ugandan Government has acknowledged that insufficient supplies and commodities is one of the key challenges facing effective delivery and utilization of effective maternal health services. The Government of Uganda renewed its commitment to Reproductive Health Commodities at the London Family Planning Summit held on July 11, 2017. These commitments included;  To reduce the unmet need for family planning to 10 percent and increase the modern contraceptive prevalence rate among all women to 50 percent by2020and;  Allocating $US 5 million annually for procurement and distribution of reproductive health/family planning supplies and commodities to the last mile.